Сучасні реалії та перспективи митного аудиту в Україні - Рябчук, Оксана Григорівна; Салямон-Міхєєва, Катерина Дмитрівна; Оксана, Рябчук (Державний податковий університет, 2023)
Дослідження присвячене аналізу сучасних реалій та перспектив митного аудиту в Україні. Основною метою дослідження є детальний розгляд важливих аспектів митного аудиту в Україні в контексті євроінтеграції та військових дій, економічного і технологічного розвитку, з виокремленням ключових викликів та можливостей удосконалення. Дослідження базується на аналізі актуальних наукових джерел та сучасних публікацій, а також на використанні мето-дів аналізу та синтезу для з’ясування суттєвих аспектів митного аудиту. Результати дослідження можуть слугувати основою для розробки та впровадження ефективних реформ у сфері митного аудиту в Україні. Практична реалізація запропонованих рекомендацій дозволить покращити якість процедур митного аудиту, забезпечити більшу відповідність міжнародним стандартам, сприятиме розвитку економіки та підвищенню прозорості в митному секторі.

The study is devoted to the analysis of modern realities and prospects of customs audit in Ukraine. The current state of customs audit in Ukraine is characterized by numerous problems, a number of which were deepened as a result of the martial law. This created additional challenges for effective control and implementation of international standards, where the state reduced economic pressures, but created opportunities for abuses and corruption to develop. In view of the situation in Ukraine, the issue requires a detailed consideration of important aspects of customs activity in the context of European integration and military operations, highlighting key challenges and opportunities. The purpose of the article is a comprehensive analysis of modern realities and prospects of customs audit in Ukraine, taking into account military, political, technological and legislative factors. The research methodology is based on the analysis of current sources and literature, as well as on the use of analysis and synthesis methods to clarify the essential aspects of the customs audit. Results. In the course of the research, numerous problems in the field of customs audit were revealed, such as fiscal orientation, unbalanced tax policy, problems of determining the customs value, non-compliance of taxation with the EU, etc. At the same time, the research process also outlined prospects for overcoming these problems, in particular through a change in fiscal orientation, reforming tax policy, using digital technologies and ensuring adequate training of specialists. In particular, the introduction of digital technologies and the optimization of procedures also have the potential to contribute to the automation and improvement of the accuracy of customs audits. In addition, ensuring adequate training of qualified specialists in this field plays an important role in improving the quality of customs audit. Conclusions. There are significant prospects for overcoming problems in the field of customs audit. It is important to change the fiscal focus in favor of more effective control and compliance with customs regulations. Reforming the tax policy, improving the system for determining the customs value and harmonizing taxation with the EU will contribute to reducing discrepancies and simplifying procedures. In the conditions of war, the state has the opportunity to reduce the tax pressure on the economy by reducing the control function, but the task of the customs audit in this case is to make sure that these inputs do not lead to abuse and corruption. Thus, the results of the study can serve as a basis for the development and implementation of effective reforms in the field of customs audit in Ukraine. Practical implementation of the proposed recom- mendations will improve the quality of customs procedures, ensure greater compliance with international standards, contribute to the development of the economy and increase transparency in the customs sector.
Keywords: митний аудит; митний пост-аудит; митний контроль; державний фінансовий контроль; воєнний стан; customs audit; customs post-audit; customs control; state financial control; martial law